Embryological understanding of fascial structures related to total mesorectal excision - Sun Yiming; Guan Helong; Sun Lingyu (结直肠肛门外科)
The core goal of total mesorectal excision (TME) is to completely resect the mesorectum surrounded by the visceral layer of the pelvic fasciae and protect pelvic autonomic nerve. Here, we sort out the embryonic development of rectum, anus, mesorectum, retrorectal space and pelvic fasciae as well as reviews the related clinical controversies, in order to provide a reference for young surgeon to correctly understand the anatomical structure of pelvic fasciae and adjacent organs of rectum and to perform TME with higher quality.